(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
A study of the state of preservation of a rare component of the flora of the site on the left bank of the middle reaches of the Dnipro River with an area of 19036,5 hectares, which is the object of the Emerald Network UA0000337 «Divychky». It is proposed to create within this national nature park. Vegetation is represented by meadow-swamp, forest-shrub-swamp and forest biotopes. There are four types of localities are dominant: shallow water areas of ancient lakes and coastal shallow waters with aquatic and coastal-aquatic vegetation; flooded segments of terraced and cavity depressions of the pine terrace with a complex of shrub-forest-meadow-swamp vegetation; lowland plain and slightly hilly segments of the pine terrace with medium-rich fresh sod-podzolic soils with oak and oak groves; uplift segments of aeolian origin with dry poorly formed soils and sands with dry forests, pine forests and psammophilous wastelands. Currently, it can be stated that 6 sozophyte species of international, 13 national and 7 regional significance are growing in the territory of the valley complex of sand terraces Dnipro-Karan. Among the protected species of European importance are populations of 6 species: Iris hungarica, Jurinea cyanoides, Ostericum palustre, Salvinia natans, Liparis loeselii, Trapa natans (the three last belong also to the Red Data Book of Ukraine). Moreover, 10 populations of species from the Red Data Book of Ukraine are registered on the mentioned area: Dactylorhiza incarnata, Daphne cneorum, Epipactis helleborine, E. palustris, Lycopodiella inundata, Lilium martagon, Neottia nidus-avis, Platanthera bifolia, Pulsatilla pratensis and Stipa borysthenica. Populations of 14 sozophyte species are represented by many localities with a high number of individuals and good indicators of the reproductive process; 6 species represent poorly due to the small number of localities and low number of individuals in populations; for populations of 3 sozophyte species (Liparis loeselii, Lycopodiella inundata, Dryopteris cristata) there is a danger of extinction due to the fact that only a few localities with a small number of individuals were found. The current state of the landscape complex of this area determines the high probability of growth of some species of sozophytes, which makes further research relevant.